Поповнення колекції ЦДІАК України - Демченко, Л. (Архіви України, 2009)
Information on the handing over of micro photocopies from the US National Archives and Records Administration to the Central State Historical Archives of Ukraine in Kyiv by the Extraordinary and Plenipotentiary U.S. Ambassador to Ukraine William B. Taylor.